Origin of prefabricated frozen elephant trunk - Haverich, Axel; Karck, Matthias (Annals of Cardiothoracic Surgery; Vol 14, No 4 (July 31, 2025): Evolution of Elephant Trunk I, 2025)
At first glance, the frozen elephant trunk (FET) appears as a disruptive innovation in aortic surgery. Like any important surgical innovations, however, be it a product or a procedure, the prefabricated, four-branched device has undergone a stepwise, iterative phase of development prior to its first clinical implantation in 2010. In parallel, the surgical procedure of aortic arch replacement itself has had to mature towards a level of quality and risk control to allow for refinement via a new device. These preparatory technical steps included mastering circulatory arrest, including brain and spinal cord protection, which required decisive innovation in extracorporeal circulation (ECC) management. In addition, patient selection with respect to age and risk factors, but also his or her underlying disease—aneurysm, dissection, atherosclerosis—has been optimized prior to the introduction of the prefabricated substitute for aortic arch replacement. Of utmost importance were those steps, taken by individual surgeons and institutions by use of self-fabricated substitutes, combining various commercially available devices. Thus, the frozen elephant technique, as applied today, did not crash into the armamentarium of unprepared aortic surgeons via device engineering and industrial product development alone. Instead, it resembles an evolutionary process, guided by a number of international institutions exploring preliminary approaches, and learning from each other via scientific exchange. This process, however, would have remained unthinkable without the tremendous advances in medical imaging via tomographic techniques, including their increasing resolution and 3D depiction. This communication will focus on the intermediary surgical steps and the technological advances between the prefabrication of the FET by the medical product industry and its first successful clinical application, as it is used today.